2023
DOI: 10.1001/jamaoncol.2022.5816
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Immune Checkpoint Inhibitors in Patients With Advanced Esophageal Squamous Cell Carcinoma

Abstract: ImportanceImmune checkpoint inhibitors (ICIs) have improved survival outcomes of patients with advanced esophageal squamous cell carcinoma in both first- and second-line settings. However, the benefit of ICIs in patients with low programmed death ligand 1 (PD-L1) expression remains unclear.ObjectiveTo derive survival data for patient subgroups with low PD-L1 expression from clinical trials comparing ICIs with chemotherapy in esophageal squamous cell carcinoma and to perform a pooled analysis.Data SourcesKaplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
34
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 27 publications
2
34
1
Order By: Relevance
“…In recent years, the Shiny method has increasingly been used not only in oncology but also in other areas of of therapeutics, such as medical devices [ 20 ], surgery [ 21 , 22 ] and also in patients with COVID-19 [ 23 ]. However, oncology and oncohematology remain the two main areas of application, where the Shiny method represents a quite simple alternative to network meta-analysis [ 8 , 9 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the Shiny method has increasingly been used not only in oncology but also in other areas of of therapeutics, such as medical devices [ 20 ], surgery [ 21 , 22 ] and also in patients with COVID-19 [ 23 ]. However, oncology and oncohematology remain the two main areas of application, where the Shiny method represents a quite simple alternative to network meta-analysis [ 8 , 9 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, PFS with nivolumab plus chemotherapy was significantly better than that with chemotherapy alone in patients with PD-L1 ≥ 1% [ 27 ]. A meta-analysis that enrolled 4752 advanced esophageal SCC patients from several randomized clinical trials reports that no significant benefit in OS was observed with immunochemotherapy compared with chemotherapy in the subgroup of patients who had a tumor proportion score lower than 1% compared with chemotherapy [ 28 ]. Because the PD-L1 detection is not reimbursement by insurance, we only chose six patients who received either first-line immunechemotherapy, second-line immunechemotherapy, or dual immune checkpoint inhibitor treatment to arrange PD-L1 immunostaining.…”
Section: Discussionmentioning
confidence: 99%
“…Factors associated with immune checkpoint inhibitor efficacy include PD-1 and PD-L1 expression, mutation burden, CD8 lymphocyte count, interferon-γ level, and interleukin 12; nevertheless, it remains challenging to accurately predict clinical efficacy ( 19 22 ). Recent meta-analysis reports on the association between PD-L1 and immune checkpoint inhibitor treatment efficacy have shown no survival benefit of immune checkpoint inhibitor-based regimens compared to chemotherapy alone in subgroups with tumor proportion scores of less than 1% ( 23 ). Further studies are required to identify predictors of treatment efficacy in this context.…”
Section: Discussionmentioning
confidence: 99%